2012
DOI: 10.1007/s10457-011-9467-3
|View full text |Cite
|
Sign up to set email alerts
|

Farming does not necessarily conflict with tree diversity in the mid-Zambezi valley, Zimbabwe

Abstract: We tested whether cultivation and fallowing have any significant effect on tree species diversity and dominance in semi-arid Zimbabwe. To this end, we quantified tree species diversity and physiognomy on two soil types (mutapo and bandati) stratified into three land-use categories, i.e., cultivated land, fallow land and woodland. Results showed that tree species diversity was significantly different on the two soil types. Tree species diversity was high on bandati soil and 2 low on mutapo soil. Results also sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Even though there are structural, spatial and temporal differences in different agroforestry systems (Nair et al 2008), tree establishment is either through planting or protection of naturally regenerating seedlings and coppices (Fifanou et al 2011). On the other hand, traditionally well understood trees with multiple benefits like provision of building materials, fruits, shade and fodder are protected by farmers so long as they do not affect the productivity of other crops (Iiyama et al 2016;Abebe et al 2013;Tambara et al 2012;Fentahun and Hager 2010). On the other hand, traditionally well understood trees with multiple benefits like provision of building materials, fruits, shade and fodder are protected by farmers so long as they do not affect the productivity of other crops (Iiyama et al 2016;Abebe et al 2013;Tambara et al 2012;Fentahun and Hager 2010).…”
Section: Hypothesesmentioning
confidence: 99%
“…Even though there are structural, spatial and temporal differences in different agroforestry systems (Nair et al 2008), tree establishment is either through planting or protection of naturally regenerating seedlings and coppices (Fifanou et al 2011). On the other hand, traditionally well understood trees with multiple benefits like provision of building materials, fruits, shade and fodder are protected by farmers so long as they do not affect the productivity of other crops (Iiyama et al 2016;Abebe et al 2013;Tambara et al 2012;Fentahun and Hager 2010). On the other hand, traditionally well understood trees with multiple benefits like provision of building materials, fruits, shade and fodder are protected by farmers so long as they do not affect the productivity of other crops (Iiyama et al 2016;Abebe et al 2013;Tambara et al 2012;Fentahun and Hager 2010).…”
Section: Hypothesesmentioning
confidence: 99%
“…and data on land‐use and management practices in each site were adopted from Tambara et al . () and Baudron et al . (, ).…”
Section: Methodsmentioning
confidence: 86%
“…While studies have primarily focused on woody species (Biodiversity Project, 2002;Baudron et al, 2008;Tambara et al, 2012a), little attention has been placed on the subterranean component of the biota (bacteria and fungi, especially) and the various interactive processes associated with it. Studies by Tambara et al (2012a) have shown that vascular plant species composition changes with age of fallowing. Some species disappear, new ones emerge, yet others persist and become dominant up to climax community stage (Tambara et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Tambara et al (2012a) have shown that vascular plant species composition changes with age of fallowing. Some species disappear, new ones emerge, yet others persist and become dominant up to climax community stage (Tambara et al, 2012a). Similarly, fungal species composition is expected to change with age of fallowing in response to shifts in host species composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation